Do birds of a feather leave the nest together? The role of sibling personality similarity in the transition to adulthood. - Yu-Chin Her; Jorik Vergauwen; Dimitri Mortelmans (PLoS ONE, 2023)
Empirical evidences on intragenerational transmission of life course have been demonstrated and that interpersonal similarity may moderate the effect. In particular, siblings who are more similar in their demographic characteristics are more likely to follow each other's life course transitions. Focusing on parental home-leaving and building upon the social influence processes and similarity-attraction effects, this study investigates whether the association between siblings' departures from the parental home increases when they are similar in the Big Five personality traits, like similarity in demographic traits. We use 28 waves of a longitudinal sample from "Understanding Society: The U.K. Household Longitudinal Study". The results of the multilevel discrete-time event-history analysis (N = 3,717 children) indicate that the association between leaving of a sibling and oneself was strengthened when they had a similar level of extraversion, particularly when they were both introverts. This implies that although introverted adolescents and emerging adults might take less initiative regarding social relationships and be more hesitant in their transition to adulthood, when a similarly introverted sibling makes such a transition, they are more inclined to do so. To conclude, the study uncovers the relationship between siblings' personality similarity and their resemblance in nest-leaving, which helps explain young adults' home-leaving decision in an era when delayed leaving is observed.